The corneomandibular reflex. Issue 3 (June 1971) - Gordon, Robert M.; Bender, Morris B.
Abstract : Seven patients are presented in whom a prominent corneomandibular reflex was observed. These patients all had severe cerebral and/or brain-stem disease with altered states of consciousness. Two additional patients with less prominent and inconsistent corneomandibular reflexes were seen; one had bulbar amyotrophic lateral sclerosis and one had no evidence of brain disease. The corneomandibular reflex, when found to be prominent, reflects an exaggeration of the normal. Therefore one may consider the corneomandibular hyper-reflexia as possibly due to disease of the corticobulbar system.